How do you solve #3x^2 + 4x + 3 = 0# by completing the square?

1 Answer
Sep 10, 2017

Answer:

#x= +-(isqrt(-5))/3-2/3#

Explanation:

Given -

#3x^2+4x+3=0#
Take the constant term to right

#3x^2+4x=-3#

Divide each term on both sides by the coefficient of #x^2#

#(3x^2)/3+(4x)/3=(-3)/3#

#x^2+4/3 x=-1#

Divide the coefficient #x#, square it and add it to both sides

#x^2+2/3 x+4/9=-1+4/9=(-9+4)/9=-5/9#

#(x+2/3)^2=-5/9#
Take square root on both sides

#(x+2/3)=sqrt(-5/9)=sqrt(-5)/3#

#x= +-(isqrt(-5))/3-2/3#